PID CONTROL OF ELECTRONIC THROTTLE FOR DRIVE BY WIRE APPLICATION - Saeed Mahfoudh Mohiri, Abdullah (UNIVERSITI TEKNOLOGI PETRONAS, 2009)
The importance of electronic throttle in modern automotive engines is obvious. The opening of the throttle blade has to be controlled. This final year project is an attempt to control the opening of the throttle blade to a certain position by tuning the parameters of PID controller. This is to eliminate the disturbances and make the electronic throttle perform more accurately. The purpose of this report is to give an overview on the method chosen to perform the control system analysis of electronic throttle for drive by wire applications. In addition, the report discusses the results obtained and the tuning procedures used to control the opening of the throttle blade. It also shows the initial steps taken in order to develop an electronic throttle control system for the project as well as representing the tools needed to develop the system based on the chosen method. A general review on PID controller and its parameters as well as the H-bridge driver and the procedure analysis is also given in this report.